Synopsis: Economy-wide impacts of the Productive Safety Net Programme (PSNP) - Filipski, Mateusz J.; Taylor, J. Edward; Abegaz, Getachew Ahmed; Ferede, Tadele; Taffesse, Alemayehu Seyoum; Diao, Xinshen (International Food Policy Research Institute, 2016)
The findings from this study reveal that, on an economy-wide ba-sis, the benefits of PSNP significantly exceed the cost of PSNP transfers. New income created by PSNP benefits households that do not receive cash transfers; these non-beneficiaries benefit as markets transmit PSNP impacts to them through local and national markets. Documenting the total benefits, including benefits to non-beneficiaries, is critical to garner support for PSNP. Our analysis shows that PSNP achieves both social and productive goals by raising income in beneficiary households while stimulating local and national production. This should be good news to both finance and social welfare ministries.